Japanese American celebration and conflict : a history of ethnic identity and festival, 1934-1990 - Kurashige, Lon, 1964- (American crossroads, 2002)
Do racial minorities in the United States assimilate to American values and institutions, or do they retain ethnic ties and cultures? In exploring the Japanese American experience, Lon Kurashige recasts this tangled debate by examining what assimilation and ethnic retention have meant to a particular community over a long period of time.